REE distribution and Nd isotope composition of estuarine waters and bulk sediment leachates tracing lithogenic inputs in eastern Canada - Casse, Marie; Montero-serrano, Jean-carlos; St-onge, Guillaume; Poirier, André (Marine Chemistry, 2019)
The rare earth element (REE) concentrations and the neodymium (Nd) and strontium (Sr) isotope compositions of the detrital fraction and authigenic FeMn oxyhydroxide coatings of marine sediments may provide valuable information for better understanding the pathways of weathering inputs and estuarine and coastal exchange processes on different time scales. Here, we present the REE concentrations and 143Nd/144Nd (expressed in epsilon units, εNd) and 87Sr/86Sr ratios of detrital and authigenic (leached FeMn oxyhydroxides) fractions from sediment core-top samples and of estuarine water samples collected in the Estuary and Gulf of St. Lawrence (EGSL) and continental shelf off southeastern Canada. The REE distribution patterns, εNd values, and 87Sr/86Sr isotopic values from the detrital fraction allow for the discrimination of sediment from continental sources in the EGSL. Sediments in the Baie des Chaleurs and on the continental shelf, which have εNd values ranging from −14.3 to −16, 87Sr/86Sr values ranging from 0.72708 to 0.71475, and low La/Yb and Gd/Yb ratios, are mainly supplied by the early Paleozoic Appalachian Mountains. In contrast, sediments in the Laurentian and Esquiman channels (εNd = −18.7 to −21.8, 87Sr/86Sr = 0.72068 to 0.72607, and high La/Yb and Gd/Yb ratios) come from the Grenvillian metamorphic rocks in the Canadian Shield, and surface sediments on the southern Labrador Shelf (εNd = −28.7, 87Sr/86Sr = 0.73062, and high La/Yb and Gd/Yb ratios) mainly originate from the Hudson Strait and Baffin Bay. The εNd values obtained from estuarine water samples and bulk sediment leachates are unradiogenic, with values ranging between −18.9 and − 21.7 and between −16.1 and − 27.2, respectively. Based on these results and the dissolved REE concentrations, we speculate that salt-induced coagulation of colloidal matter, dissolution of lithogenic sediments from the adjacent continents (notably from the erosion of the Grenville Province on the North Shore), bottom scavenging within the nepheloid layer, and brine ...